Evaluation of sorbents for high temperature removal of tars, hydrogen sulphide, hydrogen chloride and ammonia from biomass-derived syngas by using Aspen Plus. (28th February 2020) - Marcantonio, Vera; Bocci, Enrico; Ouweltjes, Jan Pieter; Del Zotto, Luca; Monarca, Danilo
Abstract: Biomass gasification is a promising technology to produce secondary fuels or heat and power, offering considerable advantages over fossil fuels. An important aspect in the usage of producer gas is the removal of harmful contaminants from the raw syngas. Thus, the object of this study is the development of a simulation model for a gasifier including gas clean-up, for which a fluidized-bed gasifier for biomass-derived syngas production was considered, based on a quasi-equilibrium approach through Gibbs free energy minimisation, and including an innovative hot gas cleaning, constituted by a combination of catalyst sorbents inside the gasification reactor, catalysts in the freeboard and subsequent sorbent reactors, by using Aspen Plus software. The gas cleaning chain simulates the raw syngas clean-up for several organic and inorganic contaminants, i.e. toluene, benzene, naphthalene, hydrogen sulphide, hydrogen chloride and ammonia. The tar and inorganic contaminants final values achieved are under 1 g/Nm 3 and 1 ppm respectively. Highlights: A simulation model for a biomass fluidized-bed gasifier was developed by Aspen Plus. The gasification model is the quasi-equilibrium approach based on Gibbs free energy minimisation. The simulation includes a gas cleaning chain simulates for several contaminants. The contaminants considered are toluene, benzene, naphthalene, H2 S, HCl and NH3 . Tars drops at 3 g/Nm 3 ; H2 S, HCl and NH3 drops at 3.7, 0.5 and 0.6 ppm respectively.